Hybridization of ZSM‐5 with Spinel Oxides for Biomass Vapour Upgrading. Issue 5 (2nd January 2020) - Atanda, Luqman; Batalha, Nuno; Stark, Terra; Tabulo, Ben; Perkins, Greg; Wang, Zhiliang; Odedairo, Taiwo; Wang, Lianzhou; Konarova, Muxina
Abstract: In this study, we report catalytic fast pyrolysis of biomass using multifunctional hybrid spinel‐oxide@zeolite catalysts prepared by using the steam‐assisted crystallization (SAC) method to create the mesoporous zeolite followed by urea hydrolysis of metal nitrates to deposit spinel‐oxides. This hybrid catalyst was quite effective in the deoxygenation of pinewood sawdust pyrolysis vapours, while avoiding over cracking of the lignin precursors, which are already ideal as chemical and fuel precursors. In the first step, multiple spinel oxides MgB2 O4 (where B=Fe, Al, Ce, Ga, Cr) were screened as catalysts for the pyrolysis of pinewood sawdust and the resultant bio‐oil (bio‐oil on the water‐free basis) was assessed in terms of carbon efficiency, oxygen content and chemical composition. While all the tested spinel oxides deoxygenated the pyrolysis vapour, MgAl2 O4 and MgFe2 O4 were found to provide a well‐balanced deoxygenation degree and producing bio‐oil with acceptable carbon efficiency. Catalytic activity and product distribution were affected by the density and strength of the acid sites of the spinel oxides. Subsequently, CFP over MgFe2 O4 @ZSM5 and MgAl2 O4 @ZSM5 was investigated under similar condition. The better performance of the hybrid catalyst was attributed to the deposition of small particles of MgFe2 O4 in the external surface of the zeolite. The presence of this spinel oxide on the external surface depolymerized bulky oxygenates to lighter fractions that could easily access the active sites within the mesoporous structure of the zeolite, thus providing the catalytic function needed for the oxygen removal after aromatic ring saturation. Abstract : Biomass vapour upgrading : Hybrid catalyst comprising of spinel‐oxide@zeolite is developed for the catalytic fast pyrolysis of biomass. Metals in MgB2 O4 (where B=Fe, Al, Ce, Ga, Cr) has been found to influence to the deoxygenation and catalytic cracking reactions of the intermediate pyrolysis products and thus affecting the bio‐oil quality and product distribution. Among all spinel oxides, MgFe2 O4 was found to be the most effective in terms of oxygen removal efficiency.